Influences affecting employee happiness at work of private companies in Bangkok - Uthai, Prasong; Tangwannawit, Pattanan; Yospan, Chontida; Eakpamitsin, Wattana; Thongsuk, Sittisak; Sungjapo, Prakrongkwan (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research aimed to study the work happiness of private company employees in Bangkok, classified by personal factors. The population consisted of 6,204,652 private company employees in Bangkok. A sample size of 400 individuals was obtained using convenience sampling. The research instrument used was a questionnaire. Data were analyzed using frequency, mean, percentage, standard deviation, t-test, and one-way analysis of variance. The research findings revealed that the work happiness of private company employees in Bangkok differed significantly based on personal factors such as gender, age, marital status, business type, and job position, at the .01 level of significance. Article history: Received 20 September 2024 Revised 6 April 2025 Accepted 8 April 2025 SIMILARITY INDEX = 12.96 %.